Two Stages of N‐Deficient Cultivation Enhance the Lipid Content of Microalga Scenedesmus sp. (21st February 2015) - Li, Xiaomei; Wang, Mingzi; Liao, Xinhui; Chen, Han; Dai, Youfen; Chen, Bilian
Abstract: Scenedesmus sp. 14‐3 was identified as a suitable candidate for producing biodiesel. The present work studied the effects of nitrogen concentration on the biomass and lipid productivity of algae, the consumption of sodium nitrate, and the two‐stage N‐deficient cultivation that could enhance dramatically the accumulation of biomass and lipids of Scenedesmus sp. 14‐3. The two‐stage N‐deficient cultivation was described as follows: microalga Scenedesmus sp. 14‐3 was cultured under low light intensity (LL) for 10 days in an N‐deficient medium by 20 % inoculum concentration, and transferred to complete N‐depletion BG11 under high light intensity (HL) for 8 days. The highest lipid content of Scenedesmus sp. 14‐3 was 53.05 ± 0.08 % (10 % inoculum concentration) following the second stage of N‐deficient cultivation after 8 days. For the second stage of N‐deficient cultivation, the lipid content of Scenedesmus sp. 14‐3 was 49.85 ± 0.22 %, which was 1.8 times higher than that under low light intensity (LL) (46–48 μmol m −2 s −1 ) in 10 days. Meanwhile, the high algal biomass productivity was around 0.10 g L −1 day −1 after the first stage of N‐deficient cultivation (10 days) and the biomass productivity was around 0.037 g L −1 day −1 under the second stage of N‐deficient cultivation (8 days). The comparison under different culture conditions showed a significant effect of the two‐stage of N‐deficient cultivation on lipid accumulation of Scenedesmus sp. 14‐3. The two‐stage N‐deficient cultivation without centrifugation achieved a complete N‐depletion condition, but the two‐stage process required centrifugation which is unsuitable for commercialization and large‐scale utilization. In summary, two‐stage N‐deficient cultivation is a more suitable and effective culture method for commercial applications and dramatic accumulation of lipids than the two‐stage process.